GROWTH AND YIELD PERFORMANCE OF SORGHUM (Sorghum bicolor L. Moench) VARIETIES UNDER VARYING UREA REGIMES IN THE SOUTHERN GUINEA SAVANNAH ZONE OF NIGERIA - Ilozobhie, Nicholas Eronmonsele; Mbong , Blessing C.; Chorio, Timothy P.; Ushie , Faith T.; Usman, Ejura; Aihebhoria , Daniel Osabhe; Sani, Adamu (FUDMA Journal of Sciences, 2025)
Limited soil fertility and nitrogen fertilizer access hinder sorghum grain production in sub-Saharan Africa significantly. In 2022 and 2023, two field experiments were conducted at the University of Abuja's farm to evaluate the impact of varying Urea levels on sorghum growth and yield in the Southern Guinea Savannah zone, in conjunction with uniform application of phosphorus and potassium. A Randomised Complete Block Design (RCBD) with 3 replications and a 4 x 5 factorial design was used, involving 4 sorghum types (Samsorg-48, 49, 46, 53) and 5 Urea levels (0-200 kg/ha). Data collected included plant height, leaf count, leaf area, tiller count, and grain yield, to assess the impact of Urea on sorghum growth and productivity. The ANOVA results showed that both sorghum varieties and Urea applications significantly (p
Keywords: Fertiliser; Growth; Sorghum varieties; Urea levels; Yields